The Serotonin Transporter and Early Life Stress: Translational Perspectives - Houwing, Danielle J.; Buwalda, Bauke; van der Zee, Eddy A.; de Boer, Sietse F.; Olivier, Jocelien D. A. (Frontiers in Cellular Neuroscience, 2017)
The interaction between the serotonin transporter (SERT) linked polymorphic region (5-HTTLPR) and adverse early life stressing (ELS) events is associated with enhanced stress susceptibility and risk to develop mental disorders like major depression, anxiety and aggressiveness. In particular, human short allele carriers are at increased risk. This 5-HTTLPR polymorphism is absent in the rodent SERT gene, but heterozygous SERT knockout rodents (SERT+/-) show several similarities to the human S-allele carrier, therefore creating an animal model of the human situation. Many rodent studies investigated ELS interactions in SERT knockout rodents combined with ELS. However, underlying neuromolecular mechanisms of the (mal)adaptive responses to adversity displayed by SERT rodents remain to be elucidated. Here, we provide a comprehensive review including studies describing mechanisms underlying SERT variation x ELS interactions in rodents. Alterations at the level of translation and transcription but also epigenetic alterations considerably contribute to underlying mechanisms of SERT variation x ELS interactions. In particular, SERT+/- rodents exposed to adverse early rearing environment may be of high translational and predictive value to the more stress sensitive human short-allele carrier, considering the similarity in neurochemical alterations. Therefore, SERT+/- rodents are highly relevant in research that aims to unravel the complex psychopathology of mental disorders. So far, most studies fail to show solid evidence for increased vulnerability to develop affective-like behavior after ELS in SERT+/- rodents. Several reasons may underlie these failures, e.g. 1) stressors used might not be optimal or severe enough to induce maladaptations, 2) effects in females are not sufficiently studied and 3) few studies include both behavioral manifestations and molecular correlates of ELS-induced effects in SERT+/- rodents. Of course, one should not exclude the (although unlikely) possibility of SERT+/- rodents not being sensitive to ELS. In conclusion, future studies addressing ELS-induced effects in the SERT+/- rodents should extensively study both long-term behavioral and (epi)genetic aspects in both sexes. Finally, further research is warranted using more severe stressors in animal models. From there on, we should be able to draw solid conclusions whether the SERT+/- exposed to ELS is a suitable translational animal model for studying 5-HTTLPR polymorphism and stress interactions